Pacifism and nonviolence in contemporary Islamic philosophy: mapping the paths of peace - Woerner-Powell, Tom (Cambridge University Press, 2025)
In Pacifism and Nonviolence in Contemporary Islamic Philosophy, Tom Woerner-Powell combines historical analysis and contemporary interviews with Muslim peace advocates in an effort to develop an empirically grounded survey of Islamic philosophies of nonviolence and a general analysis of the phenomenon. The first monograph on Islamic nonviolence to engage substantively with contemporary debates in the field of moral philosophy, his study is critical and descriptive rather than apologetic and polemical. His approach is both multidisciplinary and interdisciplinary. Drawing on methods from the fields of peace studies, Islamic studies, and moral philosophy, he identifies, critiques, and addresses the shortcomings within the dominant approaches in these fields regarding the question of pacifism and nonviolence in contemporary Islam. Woerner-Powell's book sheds new light not only on Islamic cases of nonviolence but also on the manner in which Islamic thought might play a larger role in secular and inter-religious debates. This title is also available as open access on Cambridge Core.